ANALISIS PERBANDINGAN KUAT TEKAN BETON YANG MENGGUNAKAN PASIR GUNUNG GALUNGGUNG TASIKMALAYA DAN PASIR GUNUNG KAYAMUTH GARUT - Muhammad Dewa, Febri; Nurdianto, Risnandar (Universitas Perjuangan Tasikmalaya, 2023)
Abstract— In Indonesia, the development of an increasingly modern infrastructure development mostly uses concrete as a construction material. In Tasikmalya city there is sand mining produced from the eruption of mount Galunggung which is used as a concrete material. Besides that, there is sand that is used by the people of Malangbong sub-district, Garut Regency, namely sand dug from mount kayamuth. Therefore 18 normal concrete specimens were made, to determine the high compressive strength and the high compressive strength value of each mixture. The fine aggregate used in this research was Galunggung Tasikmalaya Mountain sand and Kayamuth Garut Mountain sand. The research method used in this study is an experimental method in the laboratory. The aim of this research is to determine the design of concrete mixtures with concrete quality fc’24,90 MPa, concrete compressive strength values at 3, 7, and 28 days, to compare the concrete compressive strength results from the two areas of sand, and which sand is better for concrete mixtures. The results of the concrete compressive strength test on the sand of Galungung Tasikmalaya Mountain at the age of 28 days of concrete is 26,28 MPa. And on the sand of Kayamuth Garut Mountain at the age of 28 days of concrete is 20,21 MPa. The result of the comparison at the differences between the sands at the age of 3, 7, and 28 days were 3,76 MPa, 2,02 MPa, and 6,07 MPa. Based on the result of concrete compressive strength, sand Galunggung Tasikmalaya Mountain is the best for mixing concrete. Keywords — Galunggung Tasikmalaya mountain sand, Kayamuth Garut mountain sand, Concrete quality fc’24,90 MPa, Concrete compressive strength. Abstrak— Di Indonesia perkembangan pembangunan infrasturktur yang semakin modern kebanyakan menggunakan beton sebagai bahan konstruksinya. Di kota Tasikmalya terdapat penambangan pasir yang dihasilkan dari letusan Gunung Galunggung yang digunakan sebagai material beton. Selain itu ada pasir yang dimanfaatkan oleh masyarakat Kecamatan Malangbong Kabupaten Garut yaitu pasir galian dari Gunung Kayamuth. Oleh karena itu dibuat 18 benda uji beton normal, untuk mengetahui niali kuat tekan dari masing-masing campuran. Agregat halus yang digunakan dalam penelitian ini adalah pasir Gunung Galunggung Tasikmalaya dan pasir Gunung Kayamuth Garut. Metode penelitian yang digunakan dalam penelitian ini adalah metode eksperimen di laboratorium. Penelitian ini bertujuan untuk menentukan desain campuran beton dengan mutu beton fc'24,90 MPa, nilai kuat tekan beton pada umur 3, 7, dan 28 hari, membandingkan hasil kuat tekan beton dari kedua pasir, dan pasir mana yang lebih baik untuk campuran beton. Hasil uji kuat tekan beton pasir Gunung Galungung Tasikmalaya pada umur beton 28 hari adalah 26,28 MPa. Dan pada pasir Gunung Kayamuth Garut pada umur beton 28 hari adalah 20,21 MPa. Hasil perbandingan selisih antara pasir pada umur 3, 7, dan 28 hari adalah 3,76 MPa, 2,02 MPa, dan 6,07 MPa. Berdasarkan hasil kuat tekan beton, pasir Gunung Galunggung Tasikmalaya paling baik untuk campuran beton. Kata kunci — Pasir gunung Galunggung Tasikmalaya, Pasir gunung Kayamuth Garut, Mutu fc’24,90 MPa, Kuat tekan beton.